THE GROWTH STATUS OF QUANTITY SURVEYING FIRMS IN SOUTH-WESTERN, NIGERIA : MANAGEMENT EXECUTIVE’S PERSPECTIVE - Moyanga, Dorcas Titilayo; Agboola, Ajoke A. (Journal of Surveying, Construction and Property, 2020)
Quantity surveying firms (QSFs) in Nigeria are faced with numerous challenges and stiff competitions in the construction industry that have really threatened the growth and survival of the firms. Therefore, this study examined the current growth status of QSFs in Lagos and Ondo States, Nigeria. This was achieved by assessing some germane growth indicators of firms which include asset, profit, staffing, clients and so on. Descriptive research design was adopted through a census survey of all quantity surveying firms in the study area. Questionnaires were distributed to top management executives of the firms and the data adequately analysed using analysis of variance (ANOVA) to compare the growth indicators (at startup level and current level) and test statistic F was computed to test hypotheses. It was revealed that QSFs have not been experiencing growth in the number of employees, number of clients and asset owned by the firms. Furthermore, there is decrease in profit which is the indicator that most determines firm’s growth. Therefore, the study recommends that QSFs in Nigeria should maximize their profit level so that employees’ strength and salary are not affected since QSFs depends on the skill of quantity surveyors in order to succeed and survive.